First-principles investigation of two-dimensional covalent–organic framework electrocatalysts for oxygen evolution/reduction and hydrogen evolution reactions. Issue 21 (11th October 2021) - Ji, Jing; Zhang, Cunjin; Qin, Shuaibo; Jin, Peng
Abstract : Covalent–organic frameworks containing different metal centers are promising electrocatalysts for the OER, ORR and HER with rather low theoretical potentials. Abstract : The oxygen evolution reaction (OER), oxygen reduction reaction (ORR), and hydrogen evolution reaction (HER) all have attracted much attention due to their utmost importance for clean and renewable energy applications. As emerging versatile nanomaterials, covalent–organic frameworks (COFs) can serve as OER/ORR/HER electrocatalysts, but their potential remains largely underexplored thus far. In this work, based on the structure of COF-366-Co achieved in recent experiments, first-principles calculations were conducted to investigate the electrocatalytic performances of fifteen two-dimensional (2D) M-COFs (M = Sc–Zn, Ru, Rh, Pd, Ag, Ir) containing various metalloporphyrin active centers. The results reveal that all the M-COFs bear fully exposed, atomically dispersed, thermodynamically and electrochemically stable metal sites, as required by the ideal single-atom catalysts. According to the thermodynamic calculations, the Co-COF and Ir-COF are perfect OER catalysts with rather low theoretical overpotentials ( η OER : 0.38 and 0.34 V). The Mn-COF, Fe-COF, and Rh-COF are also promising for the OER ( η OER : 0.62, 0.57 and 0.51 V). Moreover, the Co-COF can readily catalyze the ORR ( η ORR : 0.23 V) as well, and is thus a potential OER/ORR bifunctional catalyst. The Mn-COF and Fe-COF are also favorable for both ORR ( η ORR : 0.50 and 0.39 V) and HER ( η HER : 0.08 and 0.10 V), and may serve as OER/ORR/HER trifunctional catalysts. Their excellent performances stem from the suitable metal d bands, which cause optimal bindings for all the key intermediate species along the reaction pathway. The current work not only finds several 2D-COFs as promising electrocatalysts, but also elucidates their exact structure–activity relationship, which is useful for the rational design of more single-atom catalysts.